2018
DOI: 10.1039/c8ay01887a
|View full text |Cite
|
Sign up to set email alerts
|

A novel fluorescent probe for Hg2+ detection in a wide pH range and its application in living cell imaging

Abstract: A novel fluorescent probe (XL-1) exhibited over 50-fold enhanced fluorescence in the presence of Hg2+ and no interference could be produced by other metal ions, anions and amino acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…As seen in Figure , when 10 μM Hg 2+ is added, the fluorescence intensity of the probe at 510 nm changes rapidly with the incubation time, reaching equilibrium after 10 min in the buffer of 0.01 M PBS (ethanol/water = 2:8, v/v; pH = 7.40). The response time of the probe to Hg 2+ was much faster than that of the previously developed Hg 2+ fluorescent probe. ,, Without Hg 2+ , the fluorescence intensity at 510 nm did not change in the system, indicating that the probe was steady under the experimental conditions. The experimental results indicate that the probe 1 can be applied for rapid determination of Hg 2+ .…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…As seen in Figure , when 10 μM Hg 2+ is added, the fluorescence intensity of the probe at 510 nm changes rapidly with the incubation time, reaching equilibrium after 10 min in the buffer of 0.01 M PBS (ethanol/water = 2:8, v/v; pH = 7.40). The response time of the probe to Hg 2+ was much faster than that of the previously developed Hg 2+ fluorescent probe. ,, Without Hg 2+ , the fluorescence intensity at 510 nm did not change in the system, indicating that the probe was steady under the experimental conditions. The experimental results indicate that the probe 1 can be applied for rapid determination of Hg 2+ .…”
Section: Resultsmentioning
confidence: 81%
“…The response time of the probe to Hg 2+ was much faster than that of the previously developed Hg 2+ fluorescent probe. 49,55,56 Without Hg 2+ , the fluorescence intensity at 510 nm did not change in the system, indicating that the probe was steady under the experimental conditions. The experimental results indicate that the probe 1 can be applied for rapid determination of Hg 2+ .…”
Section: ■ Introductionmentioning
confidence: 92%
“…Hg 2+ (1.0 × 10 –5 mol L –1 ) were added to probe 1 solution, and the change in fluorescence intensity from 0.0 to 5.0 min was recorded to examine the time response of probe 1 for Hg 2+ . From Figure , it can be observed that the complexation speed of probe 1 and Hg 2+ was very rapid, and the fluorescence intensity could reach the maximum within 60 s. The response time of the proposed probe for Hg 2+ was shorter than that of formerly reported fluorescent probes for Hg 2+ . Therefore, the fluorescent probe would be utilized for real-time Hg 2+ detection.…”
Section: Resultsmentioning
confidence: 90%
“…To date, many analytic approaches have been employed for sensing Hg 2+ such as high-performance liquid chromatography–inductively coupled plasma mass spectrometry (HPLC–ICP-MS), HPLC coupled with atomic fluorescence spectrometry (HPLC–AFS), ICP-atomic emission spectrometry (ICP-AES), atomic absorption spectrometry (AAS), ultraviolet–visible absorption spectrometry (UV–vis), fluorometry, , electrochemical methods, , and so on. Among all the methods developed, fluorometry possess remarkable advantages because of its high sensitivity, inherent simplicity, instrument operability, in situ detection, and bioimaging analysis in vivo. , Hitherto, many fluorescent probes had been constructed to determine Hg 2+ . However, some analytical performances of these probes are unsatisfactory, including the slow response time, cross interference, , poor sensitivity, and so forth. Therefore, novel Hg 2+ fluorescent probes are still desirable, which possess fast response speed, excellent selectivity, and sensitivity.…”
Section: Introductionmentioning
confidence: 99%